Oliver Platt with male and two female students in The Sea (Tufts Archival Research Center, 2014)
slide (photograph). Director: Sherwood Collins. Oliver Platt (back, middle) and two students observe an unidentified object, while a third student is laying down in a scene from a university production of The Sea.